Convergent Total Synthesis of (±)-Apomorphine via Benzyne Chemistry: Insights into the Mechanisms Involved in the Key Step - Muraca, Ana Carolina A.; Perecim, Givago P.; Rodrigues, Alessandro; Raminelli, Cristiano (Synthesis, 2017)
Convergent total synthesis of (±)-apomorphine hydrochloride was accomplished by an approach that employs in the key step a sequence of transformations involving a [4+2]-cycloaddition reaction followed by a hydrogen migration. Through this sequence of transformations, the desired aporphine core was obtained regioselectively in 75% isolated yield. Since only one regioisomer was produced in the key step of the synthesis, a polar [4+2]-cycloaddition mechanism was proposed. Furthermore, NMR experiments and theoretical calculations were carried out to elucidate the hydrogen migration mechanism. (±)-Apomorphine hydrochloride was achieved after 9 steps in an overall yield of 8% involving benzyne chemistry.
Keywords: (±)-apomorphine; aporphine core; benzyne chemistry; mechanisms; NMR experiments; theoretical calculations